‘The darker angels of our nature’: Early Bronze Age butchered human remains from Charterhouse Warren, Somerset, UK - Schulting, Rick J.; Fernández-Crespo, Teresa; Ordoño, Javier; Brock, Fiona; Kellow, Ashleigh; Snoeck, Christophe; Cartwright, Ian R.; Walker, David; Loe, Louise; Audsley, Tony (Cambridge University Press (CUP), 2025)
Direct physical evidence for violent interpersonal conflict is seen only sporadically in the archaeological record for prehistoric Britain. Human remains from Charterhouse Warren, south-west England, therefore present a unique opportunity for the study of mass violence in the Early Bronze Age. At least 37 men, women and children were killed and butchered, their disarticulated remains thrown into a 15m-deep natural shaft in what is, most plausibly, interpreted as a single event. The authors examine the physical remains and debate the societal tensions that could motivate a level and scale of violence that is unprecedented in British prehistory.
Keywords: Archaeology; 4301 Archaeology; South-west England; Beaker; violence; cutmarks; cranial trauma; cannibalism